Inequality, violence, and ecology in Brazil - Maria Cecília de S. Minayo
This paper studies the articulation of three subjects - ecology, inequality, and violence - as interconnected components of reality, in such a way that each of the three interferes in the whole. At a time of increased ecological awareness, this paper shows that poverty, destination, and violence not only affect the environment, but that they are also responsible for the destruction of culture and life in society. Furthermore, as a cry for Nature, this increased awareness represents a struggle for life with dignity for all.